Does Portfolio Diversification Affect Performance of Balanced Mutual Funds in Kenya? - Iraya, Cyrus; Wafula, Fernandes Juma (European Scientific Journal, ESJ, 2018)
Literature provides conflicting results on the effect of diversification on performance of mutual funds with some studies showing a positive relationship (Markowitz, 1952; Muriithi, 2005; Kagunga, 2010), others negative (Chang & Elyasiani, 2008; Fiegenbaum & Thomas, 1998) and still others showing that there is no relationship between the two variables (Loeb, 1950). It is with this background that this study sought to establish the effect of diversification on performance of mutual funds in Kenya. The study took a descriptive research design approach on weekly performance of a sample of 7 balanced mutual funds for the year 2013.The study used secondary data sources available at the Capital Market Authority offices and from each mutual funds. The portfolio return was determined by computing the changes in prices of the balanced fund as traded at the Nairobi Securities Exchange (NSE) while diversification was determined from the level of Unsystematic Risk in the Performance. The study used the Ordinary Least Squares (OLS) multiple linear regression equation. Control variables of the size and age of the fund were introduced in the regression model. The results indicated the existence of a positive relationship between the Unsystematic Risk and Performance of balanced mutual funds with a beta coefficient of 0.069 (t=4.971, p < 0.5. This implies that the lower the diversification the higher the performance of mutual funds.